Penetration resistance of aluminium foam. (5th April 2005) - Li, Q.M.; Maharaj, R.N.; Reid, S.R.
The resistance of aluminium foam against projectile penetration has been studied experimentally and analytically and the results are presented in this paper. The penetration depth of a rigid, flat-nosed projectile into an aluminium foam target was measured at various impact velocities between 20 m/s and 120 m/s. An analytical model based on crushing stress shock enhancement theory is presented to offer estimation for the penetration depth into aluminium foam target by such a projectile.